Lane change aspect ratio and dimensionless path for emergency obstacle avoidance - Phuman Singh, Amrik Singh; Abu Kassim, Khairil Anwar; Koetniyom, Saiprasit; Ubaidillah, Ubaidillah (Praise Worthy Prize, 2022)
–This paper focused on the use of the nondimensionalization approach in autonomous collision avoidance, while taking into consideration five functions, namely circular arcs, ramp sinusoidal, and polynomials (quintic, septic, and cubic), for emergency lane-change manoeuvres.The aspect ratio, which is the ratio of the total longitudinal distance to the total lateral distance during a lane change, was obtained for each function. The dimensionless vehicle velocity is a single function that combines the vehicle velocity, total lateral distance for lane change, and tyre-road friction coefficient. The aspect ratio was plotted against the dimensionless vehicle velocity to obtain a dimensionless decision-making diagram. The intersection point between the curves produced by the autonomous emergency braking and autonomous emergency steering was identified for each decision-making diagram. Among the five functions, the circular arcs achieved the smallest aspect ratio, while the septic polynomial gave the largest aspect ratio. The dimensionless decision-making diagram may serve as a useful tool for the study of autonomous collision avoidance manoeuvres